Implementasi Total Quality Management (TQM) Pada Koperasi Syari’ah Di Kabupaten Lombok Utara - Sari, Dian Aulia Mutia; Mansur, Zainuddin; Mulhimmah, Baiq Ratna (Universitas Mataram, 2024)
The purpose of this study is to analyze the implementation of Total Quality Management (TQM) in Sharia Cooperatives in North Lombok Regency. The research method used is qualitative research. The research data is described or explained in the form of descriptions according to the actual situation. There are two sources of data in this study, namely primary data and secondary data. Data collection techniques are carried out by observation, interviews and documentation. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions or verification. The results of this study indicate that the implementation of Total Quality Management (TQM) in Sharia Cooperatives in North Lombok Regency is carried out by referring to the management function itself which includes planning, organizing, actuating and controlling which are carried out effectively and efficiently. In addition, the implementation of Total Quality Management (TQM) (society), respect for people, management based on facts and continuous or ongoing improvement and implementing standard operating procedures in cooperative management.